Struktur komunitas tumbuhan air di Rawa Mayo, Distrik Kurik, Provinsi Papua Selatan - Merly, Sendy Lely; Pangaribuan, Rosa D; Ndawi, Bernadus Mezak (AGRICOLA, 2023)
Mayo Swamp is located in Jaya Makmur Village Kurik 4 Kurik District, Regency of Merauke, South Papua Province. It has the potential of aquatic plant which is never exposed and never been studied before. This study aims to identify the species, community structure, and important valur index. The method used in this research is purposive sampling methods, through this method the quadrant 5 x 5m placed in 3 research station, and the total of quadrant was 25 quadrants. Sampling and Analysis held for three months start in August until October 2021. The results show that 4 spesies of aquatic plants successfully identified there are Nephrolepis sp., Stenochlaena palustris (Lemidi), Typha angustifolia (Lidi Air), Nelumbo nucifera (Lotus). Community structure of aquatic plants in mayo Swamps consist of diversity index (H’) the highest is 1,31 and lowest is 0,11 and categorized in low diversity. Eveness index (E) in stasiun I is the highest (0,18), meanwhile in station II and III is 0,3 and cetagorized as low. Furthermore, for Dominance Index (D) the highest goes to station II with 0,75 wand the lowest in station III with 0,29 and it can be concluded that the dominance indez of aquatic plaants in Mayo Swamp Waters in low. Along with that Important Value Index (IVI) was in the same category and species with the higher number of IVI is Stenochlaena palustris (Lemidi) with 95,483.